Factors Associated with Patient Satisfaction at Kalideres Community Health Center, West Jakarta - Krestanti, Yeni Padmini; Endarti, Ajeng Tias; Djaali, Nur Asniati (LPPM Universitas Mohammad Husni Thamrin, 2025)
Marketing strategies are used to ensure business success, including in the healthcare sector, which now faces intense competition among hospitals, clinics, and community health centers. Community health centers, as the primary government healthcare facilities, play a crucial role in providing first-level services. Patient satisfaction is a key indicator of service quality in primary healthcare facilities, including community health centers (puskesmas). Preliminary observations at Kalideres Community Health Center, West Jakarta, showed a satisfaction level of 77.8%, although complaints regarding waiting time, facility completeness, and cleanliness were still reported. Sociodemographic factors, BPJS insurance membership, and visit frequency may influence patients’ perceptions and expectations of healthcare services. This study aimed to analyze factors associated with patient satisfaction at Kalideres Community Health Center. A quantitative approach with a cross-sectional design was used. The sample consisted of 100 patients selected through non-probability incidental sampling. Data were collected using a structured questionnaire and analyzed through univariate, bivariate, and multivariate methods. Bivariate analysis showed that monthly income (p=0.005; OR=3.840; CI 1.55–9.55) and visit frequency (p=0.000; OR=11.806; CI 4.17–33.41) were significantly associated with patient satisfaction. Multivariate analysis produced a Nagelkerke R² of 0.317, identifying employment status (p=0.038; OR=2.872), income (p=0.037; OR=0.282), and visit frequency (p=0.000; OR=0.138) as significant predictors. Visit frequency was the most dominant factor influencing satisfaction. These findings recommend optimizing BPJS administrative processes, strengthening patient education regarding the benefits of regular visits, enhancing satisfaction monitoring, and improving communication quality and service delivery to support sustained patient satisfaction.